NATURAL PRODUCT MELON PULP AND ITS USE AS A NUTRIENT - qizi, Barno Norboyeva Bahodir (PT. Antis International Publisher, 2024)
Objective: This study explores the nutritional composition, health benefits, and traditional and modern uses of melon pulp, known as qovun qoqi, a culturally significant food in Central Asia. Methods: A descriptive analytical approach was utilized, examining existing literature on melon varieties (Cucumis melo L.) to assess their vitamin, mineral, and antioxidant content, alongside bioactive properties. Qualitative data analysis further contextualizes the historical significance and evolving applications of melon pulp, especially in the context of traditional preparation methods and contemporary uses in nutraceutical and cosmetic products. Results: Findings reveal melon pulp as a nutrient-dense, hydrating ingredient rich in vitamins, minerals, and antioxidants, beneficial for bodily functions, skin health, and chronic disease prevention. Notably, the study addresses challenges in its usage, such as seasonality and handling. Novelty: By synthesizing both nutritional data and cultural perspectives, this research underscores the relevance of melon pulp in modern health-focused diets and as a versatile component in natural product industries. This work contributes to the growing recognition of traditional foods in sustainable health practices, emphasizing the potential of melon pulp as a valuable, natural ingredient for diet and wellness products.